2023
DOI: 10.3390/antiox12030701
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin Interferes with the Assessment of Blood Lipid Hydroperoxide Content in Small Ruminants

Abstract: Simple and inexpensive analytical methods for assessing redox balance in biological matrixes are widely used in animal and human diagnostics. Two of them, reactive oxygen metabolites (ROMs) and total oxidant status (TOS), evaluate the lipid hydroperoxide (LOOH) content of the sample and are based on iron-mediated mechanisms. However, these tests provide uncorrelated results. In this study, we compared these two tests in the blood serum of goat kids and lambs, together with an evaluation of ceruloplasmin (CP) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The present results showed that when plasma samples were treated with sodium azide, a potent inhibitor of Cp, the analytical signal was progressively reduced in either o-D or AIS assays. Sodium azide is an inorganic compound able to bind copper, inhibiting Cp oxidase activities [37], as previously demonstrated [40][41][42]. Using sodium azide, we were able to discriminate these two methods based on the different response obtained.…”
Section: Discussionmentioning
confidence: 58%
“…The present results showed that when plasma samples were treated with sodium azide, a potent inhibitor of Cp, the analytical signal was progressively reduced in either o-D or AIS assays. Sodium azide is an inorganic compound able to bind copper, inhibiting Cp oxidase activities [37], as previously demonstrated [40][41][42]. Using sodium azide, we were able to discriminate these two methods based on the different response obtained.…”
Section: Discussionmentioning
confidence: 58%